(untitled) (Psicologia USP, 2010)
The present essay discusses the conception of the subject according to the theoretical approach of Michel Maffesoli, Professor of Sociology at Sorbonne, in Paris. The ideas of this author are very popular in some academic circles in Brazil and are disseminated through some nationwide media. However, the presuppositions that define who is Maffesolis subject are not sufficiently clarified in his works. Thus, in order to achieve the objective of this essay, an analysis of Maffesolis epistemology and ontology is performed to provide the understanding of the origins of the authors presuppositions, that is, the theories and authors on which Maffesoli built his view of the subject. With this understanding, we intend to answer the question: does Maffesolis theoretical approach indicate the existence of subject?